The female figure on the political and social poster in Catalonia (1931-1939) - González Quesada, Alfonso; Lázaro Pernías, Patricia (Historia y Comunicación Social, 2014)
This article examines the representation of the female figure in the political and social posters published in Catalonia between 1931 and 1939. A comprehensive census with 172 works has been developed and a content analysis of visual discourse was performed. The results allowed distinguishing between a symbolic use of the female figure and the representation of what has been called the ‘real woman’. During the study of this representation during the Civil War three archetypes were identified: ‘heroine- woman’, ‘victim-woman’ and ‘trap-woman’.
Keywords: women; posters; political propaganda; Spanish Second Republic; Spanish Civil War; Catalonia